ANALISIS COMPLIANCE RISK MANAGEMENT (CRM) DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK BADAN PADA KPP PRATAMA DEPOK CIMANGGIS - Muhammad, Fadel Mirojd; Sari, Dahlia (Universitas Muhammadiyah Palembang, 2023)
Implementation of Compliance Risk Management (CRM) is one of the efforts of the Director General of Taxes to increase tax compliance. The purpose of the study was to analyze the implementation of CRM in improving corporate taxpayer compliance at the Depok Cimanggis Primary Tax Service Office. Research using qualitative methods with data collection through interviews. Taxpayer compliance is analyzed based on SE-24 / PJ / 2019 and William Dunn's policy criteria. Based on the analysis, it is concluded that all stages of CRM implementation have been carried out, but the results have not been maximized because there are several obstacles; taxpayers have not complied with paying taxes because they do not understand the importance of paying taxes and there is equal treatment for those who are compliant and non-compliant in paying taxes. There have been many taxpayers registered but have not shown compliance in paying taxes so that the realization of tax revenue has not been as expected.